Comparison of Survival Outcomes of Lymphovascular Space Invasion-Negative and Lymphovascular Space Invasion - Positive Women with Stage IIIC Endometrioid Endometrial Cancer: A Case - Control Study - Zeliha Firat Cuylan; Mehmet Mutlu Meydanli; Murat Öz; Ahmet Taner Turan; Ozgur Akbayir; Murat Dede; Ali Ayhan (Gynecology Obstetrics & Reproductive Medicine)
Objective: The purpose of this case-control study was to investigate the effect of lymphovascular space invasion on recurrence patterns and survival in patients with stage IIIC endometrioid type endometrial cancer.